2000
DOI: 10.1111/0272-4332.205067
|View full text |Cite
|
Sign up to set email alerts
|

From Breeder Reactors to Butterflies: Risk, Culture, and Biotechnology

Abstract: Social theories of risk suggest that a combination of scientific and cultural perspectives converge to influence risk perception. This article first surveys sociological perspectives suggesting that risks from modern technological development have become predominant concerns in the social consciousness. Particular attention is given to those theses describing how social elements work to create perception of risks in relation to new technologies. The themes that emerge from this survey are then related to conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Opponents of GM food and fiber products argue that the impacts on human and animal health and the environment cannot be ignored (Lomax 2000). It has been observed that GM microorganisms are living organisms that can disperse to other habitats and multiply (Seidler and others 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Opponents of GM food and fiber products argue that the impacts on human and animal health and the environment cannot be ignored (Lomax 2000). It has been observed that GM microorganisms are living organisms that can disperse to other habitats and multiply (Seidler and others 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The objectivity of science was increasingly challenged by arguments about the constructed nature of knowledge, and the ambiguous nature of complex real-world change and, as a consequence, it was increasingly recognised that the contextualised knowledge of 'non-experts', developed through real experience of societal behaviour and values, is an important source of information about the realities of risk (Beck 1992;Jasanoff 1999;Wynne 1996). Douglas and Wildavsky's (1982) theory that alternative interpretations and acceptabilities of risk are the product of personal cultural traits, which often reflect social structures, has underpinned studies that have attempted to show that the culture of scientific institutions is different from that of a general public or a local farmer (Finucane 2002;Finucane and Holup 2005) and, furthermore, that social interactions reinforce cultural barriers (Herring 2007;Lomax 2000;Priest, Bonfadelli, and Rusanen 2003) and 'amplify' risks (Kasperson et al 1988). In relation to understandings of risk, an extensive body of literature considers the ways in which cultural barriers are strengthened through the development of public distrust of regulating institutions (Lomax 2000;Priest 2001;Renn et al 1992;Renn and Levine 1991).…”
Section: Background: Tracing a Complex Trajectory In Risk Studiesmentioning
confidence: 99%
“…Douglas and Wildavsky's (1982) theory that alternative interpretations and acceptabilities of risk are the product of personal cultural traits, which often reflect social structures, has underpinned studies that have attempted to show that the culture of scientific institutions is different from that of a general public or a local farmer (Finucane 2002;Finucane and Holup 2005) and, furthermore, that social interactions reinforce cultural barriers (Herring 2007;Lomax 2000;Priest, Bonfadelli, and Rusanen 2003) and 'amplify' risks (Kasperson et al 1988). In relation to understandings of risk, an extensive body of literature considers the ways in which cultural barriers are strengthened through the development of public distrust of regulating institutions (Lomax 2000;Priest 2001;Renn et al 1992;Renn and Levine 1991). Lash and Wynne (1992) argue, along with a large body of more recent sociology literature (Finucane and Holup Irwin and Michael 2003;Pellizzoni 2010;Stirling 2003), that it is in these barriers and social and cultural practices that risks are socially constructed.…”
Section: Background: Tracing a Complex Trajectory In Risk Studiesmentioning
confidence: 99%
“…According to theories of risk, risk perception is influenced by scientific as well as cultural perspectives (Lomax, 2000). People do respond to different applications of technology differently, depending upon their perception of the utility and risk associated with a particular technology.…”
Section: Risk Management and Societymentioning
confidence: 99%